Whose Lives Matter? Race, Space, and the Devaluation of Homicide Victims in Minority Communities. Issue 3 (July 2021) - White, Kailey; Stuart, Forrest; Morrissey, Shannon L.
The recurring, horrific deaths of minority residents at the hands of police officers and vigilantes have led social movements and international protests to amplify the charge that whereas the loss of White lives is seen as tragic, the loss of Black and Hispanic lives is treated as normal, acceptable, and even inevitable. Building on and advancing theories of "color-blind racism, " the authors examine the process by which the news media uphold and reify the devaluation of Black and Hispanic lives through ostensibly race-neutral language, story lines, and cultural narratives. Drawing on an original data set containing all news articles ( n = 2, 245) written about every homicide victim ( n = 762) in Chicago, Illinois, during 2016, the authors use multilevel models to assess the extent to which victims' race and neighborhood racial composition are associated with the level of attention, or "newsworthiness, " devoted to their deaths. Using two measures of newsworthiness—the amount of coverage and recognition of "complex personhood"—the authors find that victims killed in predominantly Black neighborhoods receive less news coverage than those killed in non-Hispanic White neighborhoods. Those killed in predominantly Black or Hispanic neighborhoods are also less likely to be discussed as multifaceted, complex people. Our analyses underscore the importance of place, especially the racialization of place, in determining which victims are treated as newsworthy. These findings carry important implications for understanding and addressing color-blind racism, news-reporting practices, and territorial stigma in the reproduction of racist ideologies.